1971
DOI: 10.1017/s0021859600023558
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between soil phosphorus and response by sugar beet to phosphate fertilizer on mineral soils

Abstract: Results of two groups of experiments testing phosphate fertilizer for sugar beet were re-examined; there were 53 experiments made between 1957 and 1960 in group 1 and 25 experiments between 1957 and 1959 in group 2. The mean response of total sugar to 126 kg/ha P a O 6 was only 160 kg/ha but on a few fields response exceeded 1000 kg/ha. Response seemed to be greater in 1958 than in the other years, but between-site variance accounted for most of the difference from year to year.Stored soil samples were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
1

Year Published

1977
1977
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
(9 reference statements)
2
6
1
Order By: Relevance
“…The responses to fresh P on soils with 9, 15 and 25 mg P/kg in Table 11 agree remarkably well with those of Draycott et al (1971) who found a response of 1-3 t/ha for a few soils near 10 mg P/kg and much smaller increases, 0-3 and 0-2 t/ha, at soluble P values of 11-15 and 16-25 mg/kg respectively. Our results support the recommendation made by Draycott et al (1971) that only small insurance dressings of P are needed for sugar beet grown on soils with more than 15 mg soluble P/kg.…”
Section: Sugar Beetsupporting
confidence: 85%
See 3 more Smart Citations
“…The responses to fresh P on soils with 9, 15 and 25 mg P/kg in Table 11 agree remarkably well with those of Draycott et al (1971) who found a response of 1-3 t/ha for a few soils near 10 mg P/kg and much smaller increases, 0-3 and 0-2 t/ha, at soluble P values of 11-15 and 16-25 mg/kg respectively. Our results support the recommendation made by Draycott et al (1971) that only small insurance dressings of P are needed for sugar beet grown on soils with more than 15 mg soluble P/kg.…”
Section: Sugar Beetsupporting
confidence: 85%
“…The average response to this P dressing in our experiments, 710 kg sugar/ha, was much larger than that, 140-200 kg/ha, reported by Draycott et al (1971). However, 25% of our soils had less than 9 mg soluble P/kg whereas only 6 % of their soils were in this category.…”
Section: Sugar Beetcontrasting
confidence: 72%
See 2 more Smart Citations
“…Detrimental effects of P fertilization at excessive soil P levels have been reported (6,5) but not all data support these conclusions (12). Increasing fertilizer costs have also made it essential that growers have adequate guidelines upon which to base fertilizer applications.…”
mentioning
confidence: 96%